Development of the quality of reaching in infants with cerebral palsy: a kinematic study. (6th September 2017) - Boxum, Anke G; La Bastide‐Van Gemert, Sacha; Dijkstra, Linze‐Jaap; Hamer, Elisa G; Hielkema, Tjitske; Reinders‐Messelink, Heleen A; Hadders‐Algra, Mijna
Abstract : Aim: To assess development of reaching and head stability in infants at very high risk (VHR‐infants) of cerebral palsy (CP) who did and did not develop CP. Method: This explorative longitudinal study assessed the kinematics of reaching and head sway in sitting in 37 VHR‐infants (18 CP) one to four times between 4.7 months and 22.6 months corrected age. Developmental trajectories were calculated using linear mixed effect models. Motor function was evaluated with the Infant Motor Profile (IMP) around 13 months corrected age. Results: Throughout infancy, VHR‐infants with CP had a worse reaching quality than infants without CP, reflected for example by more movement units (factor 1.52, 95% CI 1.16–1.99) and smaller transport movement units (factor 1.86, 95% CI 1.20–2.90). Total head sway of infants with and without CP was similar, but infants with CP used more head movement units to achieve stability. The rate of developmental change in infants with and without CP was similar. Around 13 months, head control and reaching quality were interrelated; both were associated with IMP‐scores. Interpretation: Infants with CP showed a worse kinematic reaching quality and head stability throughout infancy from early age onwards than VHR‐infants without CP, implying that kinematically they do not grow into a deficit, but exhibit deficits from early infancy on. What this paper adds: Reaching quality improves throughout infancy in all infants at high risk (VHR‐infants). Infants with cerebral palsy (CP) show a worse reaching quality than VHR‐infants without CP. Infants with CP achieve head stability differently from infants without CP. Infants with CP exhibit kinematic reaching problems from early age onwards. What this paper adds: Reaching quality improves throughout infancy in all infants at high risk (VHR‐infants). Infants with cerebral palsy (CP) show a worse reaching quality than VHR‐infants without CP. Infants with CP achieve head stability differently from infants without CP. Infants with CP exhibit kinematic reaching problems from early age onwards. This article is commented on by von Hofsten on page1107 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=s5FD1f8Xi2s&feature=youtu.be